Investigation of innate immunity, mucosal therapeutics and pathogenesis of select agent Burkholderia species - Goodyear, Andrew Whitman, author; Dow, Steven W., advisor; Schweizer, Herbert P., committee member; Izzo, Angelo A., committee member; Lenz, Laurel L., committee member (Colorado State University. Libraries, 2012)
Burkholderia mallei and B. pseudomallei are important human pathogens and cause the diseases glanders and melioidosis, respectively. Both organisms are gram-negative bacteria and due to their potential use as bioweapons both have been classified as category B select agents by the Centers for Disease Control and Prevention (CDC). Both bacteria are highly infectious when inhaled and are inherently resistant to many antimicrobials. The protective innate immune responses to Burkholderia infection, specifically B. mallei infection, are poorly characterized. The goal of these studies was to gain a better understanding of innate immunity and pathogenesis to improve development of therapeutics for treatment of both diseases. A mouse model of acute respiratory glanders was developed to investigate the role of monocytes following B. mallei infection. Mice lacking monocyte chemoattractant protein-1 (MCP-1), or chemokine receptor 2 (CCR2), and wild type (WT) mice treated with liposomal clodronate were all highly susceptible to B. mallei infection. Following B. mallei infection neutrophil recruitment and TNF-α production remained intact in CCR2-/- mice. However, CCR2-/- mice were unable to recruit monocytes or dendritic cells, and produced less IL-12 and IFN-γ than WT mice. Treatment of CCR2-/- mice with recombinant IFN-γ (rIFN-γ) was sufficient to protect mice against disease, highlighting the importance of this cytokine for protection. To expand on these studies, the necessity of myeloid differentiation factor 88 (MyD88) dependent Toll-like receptor (TLR) signaling was investigated. TLRs are pattern recognition receptors which recognized conserved pathogen associated molecular patterns (PAMP) expressed by invading organisms. The majority of bacterial associated PAMPs recognized by TLRs signal through the MyD88 dependent pathway. MyD88-/- mice were highly susceptible to B. mallei infection, and recruitment of multiple cell types including neutrophils, monocytes and dendritic cells was impaired. Intracellular cytokine staining revealed that dendritic cells and monocytes were the major source IL-12, and natural killer (NK) cells were the major source of IFN-γ. While early production of IL-6 and TNF-α was reduced, MyD88-/- mice were completely unable to produce IFN-γ. Similar to monocyte deficient mice, treatment of MyD88-/- mice with rIFN-γ provided partial protection against infection. Therefore monocyte derived dendritic cell production of IL-12, and subsequent production of IFN-γ by NK cells is critical for protection against acute glanders infection. Treatment of glanders and melioidosis with antibiotics requires prolonged treatment, and even optimal antibiotic regimens can fail. Therefore the ability of an immune based therapeutic to protect mice following a respiratory challenge was investigated. Cationic liposome DNA complexes (CLDC) are potent activators of innate immunity and induce high levels of IFN-γ production. CLDC administration 24 hours prior to infection with either B. mallei or B. pseudomallei provided complete protection. Administration at the time of infection provided partial protection, although therapeutic treatment was not effective. The protective effect of CLDC was found to be dependent on MyD88 signaling and IFN-γ production. In contrast, neither monocyte recruitment nor nitric oxide production was necessary for CLDC protection. These studies demonstrated that prophylactic administration of CLDC could provide protection against an intentional release of either pathogen. While acute disease following B. pseudomallei has been well studied, little is known about chronic disease. Chronic disease is recognized as a major complication of melioidosis, and while disease has been reported to develop in patients up to 62 years after exposure, the site of bacterial persistence is not known. B. pseudomallei is an environmental saprophyte and therefore the potential for infection following inoculation, inhalation or ingestion exists. Despite the potential of oral infection, ingestion has not been well studied. In this study an improved selective medium was developed allowing for detection of low level enteric colonization by B. pseudomallei. A mouse model of persistent enteric B. pseudomallei infection was developed to investigate the ability of chronic melioidosis to develop following oral infection. Oral infection with B. pseudomallei resulted in bacterial persistence for up to 60 days in all gastrointestinal (GI) organs, fecal shedding, and a focus of infection localized to the mucosa of the stomach. Despite colonization of the stomach and dissemination into the distal GI tract, no tissue pathology was observed in any GI organ. Multiple B. pseudomallei strains were shown to colonize the stomach, and all strains disseminated to the spleen and liver. All mice were shedding bacteria in their feces although bacterial burdens in both GI organs and feces were low, which may make detection of GI colonization in humans difficult. These studies suggest the GI tract may be a reservoir for asymptomatic carriage of B. pseudomallei, and if confirmed in humans, could have implications for screening and treatment of melioidosis.
Keywords: Burkholderia; CLDC; enteric; innate immunity; monocytes; MyD88